1996
DOI: 10.1136/vr.138.6.128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of medetomidine with xylazine/l‐methadone in dogs

Abstract: Seventy-two healthy dogs required sedation and analgesia for a variety of procedures causing discomfort or pain. They were treated either with the alpha 2-agonist medetomidine at 40 micrograms/kg (15 intravenously and 17 intramuscularly), or 80 micrograms/kg (15 intravenously and 15 intramuscularly) or with xylazine plus l-methadone (1.0 mg)(10 intravenously). The levels of sedation, analgesia and safety were compared clinically and by measurements of the effects on the electrocardiogram (ECG) and blood gases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
3
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
4
19
3
1
Order By: Relevance
“…When methadone was administered in combination with xylazine, none of the dogs panted. These results are in contrast with a previous study in which the authors reported a prevalence of panting of 50% in dogs receiving xylazine plus methadone (Kramer et al. 1996).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…When methadone was administered in combination with xylazine, none of the dogs panted. These results are in contrast with a previous study in which the authors reported a prevalence of panting of 50% in dogs receiving xylazine plus methadone (Kramer et al. 1996).…”
Section: Discussioncontrasting
confidence: 99%
“…Four out of six dogs receiving xylazine–methadone had no pedal withdrawal reflex at least at one time point during the study compared with none of the dogs receiving xylazine alone. A previous study reported better analgesia in dogs treated with xylazine and methadone than in those treated with medetomidine alone (Kramer et al. 1996).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A shorter anesthetic recovery period occurred in G2 (48 min) as compared to G1 (52 min) and, also with a superior quality. o C what has also been reported for different dissociative anesthesia protocols through continuous infusion 2,3,4 .A greater reduction in body temperature as observed by some authors 5,6,7 is due to the peripheral vasoconstriction and blood central redistribution due to the action of a-2 agonists. This is a controversial effect for a-2 agonists lead to peripheral vasodilatation and heat production reduction.…”
Section: Resultssupporting
confidence: 58%
“…For the time of sedation and partly beyond it xylazine causes bradycardia, decreases in body temperature and breathing rate (Rector et al 1996, Ilback & Stalhandske 2003. The effects of a xylazine/levomethadone/fenpipramide combination are comparable with what is described for xylazine alone (Kramer et al 1996). Isoflurane is one of the most widely applied volatile anaesthetics in veterinary medicine and was reported in dogs to cause unwanted effects, such as depression of myocardial contractility, hypoventilation, cerebral vasodilation and triggering of malignant hyperthermia, and that it causes irritation to the respiratory tract (Galloway et al 2004).…”
Section: Discussionmentioning
confidence: 97%